Analysis of Banks-Customer Services and general Awareness in Peoples of Selective Area of Aligarh District - kumar Sharma, Dr. Jugendra (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Banks need to build relationships with customers who value more than delivering key products. Improves the ability to add material and intangible elements from core products to "peripherals." Achieving one of the prerequisites of quality and value is the quality of measurement and control technology. Keywords: strategy, marketing, finance, market dominance, manufacturing operations.